Peptidases from Maclura Pomifera for Preparation of Food Protein Hydrolysates : Purification by Single-Step Chromatography and Characterization of Pomiferin I - Reyes Jara, Andrea Milagros (2020)
Our objective was to isolate peptidases from the latex of Maclura pomifera fruits and use them to hydrolyze food proteins, as well as to purify and characterize the main peptidase. Two partially purified proteolytic extracts were prepared by ethanol (EE) and acetone (AE) precipitation from an aqueous suspension of exuded fruit latex. EE was used to hydrolyze food proteins with a ratio of 0.19 caseinolytic units (Ucas) per mg of substrate. Different values of hydrolysis degree were observed for hydrolysates of egg white, soy protein isolate, and casein at 180 min (9.3%, 31.1%, and 29.1%, respectively). AE was employed to purify a peptidase which exhibited an isoelectric point (pI) of 8.70 and whose abundance in AE was 28.3%. This enzyme was purified to homogeneity using a single-step procedure by cation-exchange chromatography, achieving an 8.1-fold purification and a yield of 16.7%. The peptidase was named pomiferin I and showed a molecular mass of 63,177.77 Da. Kinetic constants (KM 0.84 mM, Vmax 27.50 uM s−1, kcat 72.37 s−1, and kcat/KM 86.15 mM−1 s−1) were determined employing N-α-carbobenzoxy-L-alanyl-p-nitrophenyl ester as substrate. Analysis by PMF showed only partial homology of pomiferin I with a serine peptidase from a species of the same family.